The Role of Financial Constraints in the Influence of Academic Experts and Corporate Governance on Tax Avoidance - Djodi Akbar; Atik Djajanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
The tension among tax efficiency and governance integrity poses a critical challenge for firms operating in emerging markets with weak enforcement environments. The purpose of this study is to explore the impact of academic experts and Corporate Governance on corporate tax avoidance, together with the moderating role played by financial constraints. Panel data from manufacturing firms listed on the Indonesia Stock Exchange from 2020 to 2024 are analyzed using a quantitative approach. The sample consists of 51 firms with 255 observations selected through purposive sampling. The analysis is conducted using a Fixed Effects Model (FEM) with an Estimated Generalized Least Squares (EGLS) approach. The results show that academic experts and corporate governance do not have a significant effect on tax avoidance. Financial constraints have a positive and significant effect on tax avoidance. Furthermore, financial constraints moderate the relationship between academic experts and tax avoidance at the 10% significance level, with a positive direction. This finding indicates that under financial pressure, academic experts tend to support the optimization of corporate tax strategies. In contrast, financial constraints do not moderate the relationship between corporate governance and tax avoidance. These findings suggest that financial factors play a more dominant role than governance mechanisms in determining corporate tax avoidance behavior.